Sonographic appearance of a cesarean scar pregnancy with placenta percreta invading the bladder in the first trimester and management with fertility preservation. Issue 3 (24th May 2016) - Rebarber, Andrei; Varrey, Aneesha; Scherr, Doug; Fox, Nathan; Sassoon, Robert; Ciorica, Doina; Saltzman, Daniel
ABSTRACT: A 36‐year‐old, gravida 8, para 6, woman with six prior cesarean sections presented at 6 weeks with a cesarean scar pregnancy. Medical management was performed initially; however, subsequent three‐dimensional sonographic examinations revealed trophoblastic invasion into the bladder. This led to robotic‐assisted partial cystectomy, fulguration of invaded pregnancy, and repair of the uterine defect. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45 :163–167, 2017